The effects of mindfulness meditation on the well-being of Pasifika students : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Uele, Miriam F (Massey University, 2023)
Background: Mindfulness application has become a topic of interest in academic research, primarily because it has been shown to support positive well-being. Mental health disorders disproportionately affect young adults aged 15 to 24, specifically Pasifika people. To the researcher's best knowledge, a mindfulness-based intervention implemented by Pasifika University students is lacking. For such reasons, the current study addresses the research gap by introducing a feasible exploratory study that aims to consider whether participation in a brief four-week mindfulness-based stress reduction intervention (MBSR) can improve levels of subjective well-being, Pasifika identity and well-being, and mindfulness of Pasifika University students. Method: The current study involved a single-group design utilising a quantitative method. Data was collected pre-and-post MBSR intervention using three self-report psychometric measures including the Well-being Index measure (WHO-8), Pacific Identity and Well-being Revised measure (PIWBSR-35), and Five Facet Mindfulness Questionnaire (FFMQ-39). A paired samples t-test was conducted pre-and-post the MBSR intervention. Results: The findings revealed that subjective well-being, Pasifika identity and well-being were significant post-intervention. However, mindfulness scores were insignificant. A further paired samples t-test was conducted on the individual factors of Pacific identity and well-being and the individual mindfulness facets. The analysis revealed that the mindfulness observation was significant. Conclusion: It can be proposed that a mindfulness meditation intervention could be appropriate for Pasifika University students aged 18 – 24 years old. While this is the case, it is crucial to consider these findings with caution. The current pilot study is a stepping stone towards further investigations that can promote the well-being of Pasifika people.
Keywords: well-being; mindfulness-based stress reduction mediation; identity; 520304 Health psychology; 451613 Pacific Peoples psychology